Infrared Laser Desorption of Intact Nanoparticles for Digital Tissue Imaging - Stiborek, Marek; Jindřichová, Lenka; Meliorisová, Stanislava; Bednařík, Antonín; Prysiazhnyi, Vadym; Kroupa, Jiří; Houška, Pavel; Adamová, Barbora; Navrátilová, Jarmila; Kanický, Viktor; Preisler, Jan (Analytical chemistry, 2022)
We report a new technique for the digital mapping of biomarkers in tissues based on desorption and counting intact gold nanoparticle (Au NP) tags using infrared laser ablation single-particle inductively coupled plasma mass spectrometry (IR LA SP ICP MS). In contrast to conventional UV laser ablation, Au NPs are not disintegrated during the desorption process due to their low absorption at 2940 nm. A mass spectrometer detects up to 83% of Au NPs. The technique is demonstrated on mapping a proliferation marker, nuclear protein Ki-67, in three-dimensional (3D) aggregates of colorectal carcinoma cells, and the results are compared with confocal fluorescence microscopy and UV LA ICP MS. Precise counting of 20 nm Au NPs with a single-particle detection limit in each pixel by the new approach generates sharp distribution maps of a specific biomarker in the tissue. Advantageously, the desorption of Au NPs from regions outside the tissue is strongly suppressed. The developed methodology promises multiplex mapping of low-abundant biomarkers in numerous biological and medical applications using multielemental mass spectrometers.
Keywords: Laser Therapy; Nanoparticles; Gold; laserová terapie; zlato; hmotnostní spektrometrie; lasery; kovové nanočástice; Metal Nanoparticles; Lasers; Mass Spectrometry; nanočástice